Human Immunotypes Impose Selection on Viral Genotypes Through Viral Epitope Specificity. (11th May 2021) - Gabrielaite, Migle; Bennedbæk, Marc; Zucco, Adrian G; Ekenberg, Christina; Murray, Daniel D; Kan, Virginia L; Touloumi, Giota; Vandekerckhove, Linos; Turner, Dan; Neaton, James; Lane, H Clifford; Safo, Sandra; et al.
Abstract: Background: Understanding the genetic interplay between human hosts and infectious pathogens is crucial for how we interpret virulence factors. Here, we tested for associations between HIV and host genetics, and interactive genetic effects on viral load (VL) in HIV-positive antiretroviral treatment-naive clinical trial participants. Methods: HIV genomes were sequenced and the encoded amino acid (AA) variants were associated with VL, human single nucleotide polymorphisms (SNPs), and imputed HLA alleles using generalized linear models with Bonferroni correction. Results: Human (388 501 SNPs) and HIV (3010 variants) genetic data were available for 2122 persons. Four HIV variants were associated with VL ( P < 1.66 × 10 –5 ). Twelve HIV variants were associated with a range of 1–512 human SNPs ( P < 4.28 × 10 –11 ). We found 46 associations between HLA alleles and HIV variants ( P < 1.29 × 10 –7 ). HIV variants and immunotypes when analyzed separately were associated with lower VL, whereas the opposite was true when analyzed in concert. Epitope binding predictions supported our observations. Conclusions: Our results show the importance of immunotype specificity on viral antigenic determinants, and the identified genetic interplay emphasizes that viral and human genetics should be studied in the context of each other. Clinical Trials Registration: NCT00867048. Abstract : We analyzed HIV and human host genetics in concert to resolve the interplay of viral and human genetics during infection. We showed that HIV genetic variants associated with different HLA alleles, and that genetic interactions affected viral load.